Psychological clinical care: therapeutic encounters with children in a daycare center - Campos, Ana Paula de Sá; Cury, Vera Engler (Paidéia (Ribeirão Preto), 2009)
This study aimed to analyze the therapeutic potential of encounters held by the researcher with children three to six years of age within the context of a daycare. Person-Centered Approach was the theoretical reference used. It is based on the therapeutic proposal of Virginia Mae Axline, known as Child Centered Ludotherapy. Children themselves set up the encounters' structure and established with the researcher a relationship similar to the clinical intervention known as On Duty Psychology. This phenomenological study adopted the construction of narratives based on therapeutic encounters held at the institution. The narratives permitted a phenomenological analysis of the intersubjective relationship experienced during encounters. Results revealed children's ability to: took the initiative to spontaneously seek for psychological help; communicate feelings regarding themselves and their problems; understand and collaborate to the construction of the psychological help relationship.